INTEGRASI ANALITICAL HIERARCHY PROCESS-FUZZY DALAM PEMILIHAN SUPPLIER - Dolly Rommer; Daniel B Paillin; Johan M. Tupan (ALE Proceeding, 2021)
This study discusses the selection of wood raw material suppliers using the AHP-F method. Problems by UD. Bless Furniture is the difficulty of determining which supplier has good performance in terms of price, quality, service, delivery, quantity determination, location as well as guarantees and claims. With many competitors and different raw material prices from each supplier. Many raw materials such as wood cracks are hollow and broken at the ends of the wood, the color of the wood, and the shape of the wood. Delivery plans that are often complained by companies where delivery is not according to the schedule in the agreement. The results of data processing carried out by the AHP fuzzy method show that the criteria that become a priority in supplier selection are the price criteria which have a weight of 0.47. By taking into account the seven criteria above, it is obtained that the supplier recommended being prioritized as the best supplier based on the highest priority weight, namely supplier C with a weight of 0,39 then supplier A with a weight of 0,37 and the third is supplier B with a weight of 0,24.